Studying The Growth Of Hybrid Mulberry Cuttings In The Kashkadarya Region (Texas Journal of Agriculture and Biological Sciences, 2026)
This article examines the establishment of bush plantations with ringed and unringed cuttings of hybrid and cultivar mulberry trees in the Kashkadarya Region. The effectiveness of horizontal planting of mulberry cuttings is also discussed